Hubungan Faktor Sikap dengan Pelaksanaan Program Pelayanan Kesehatan Usaha Kesehatan Sekolah (UKS) di SMP Muhammadiyah 4 Gadung Surabaya - Sustrami, Dya; Ambar Sari, Ninik (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
Health services in schools aim to improve skills and skills to take healthy living in order to form a healthy life behavior, increase the immune system of learners against disease and prevent disease, stop the disease process and prevention of disease complications. Health Services UKS need to pay attention to several factors, including predisposing factors that include attitude, knowledge. Behavior change is based on positive knowledge and attitude that will cause long lasting behavior. The research was conducted in SMP Muhammadiyah 4 Gadung Surabaya. Quantitative research with sample technique using Probability Sampling technique with simple random sampling counted 155 respondents. Instruments using questionnaires. Data were analyzed by spearman rank's and pearson's correlation test. Independent variable is attitude factor, and dependent variable is health service program implementation. The result of p = 0,000 (p value <0,05) hence concluded there is relation between attitude factor with health service of UKS. The implications of this study are the positive attitudes of pupils affecting the implementation of the health services of the UKS so that the role of pupils and implementing teachers can advance the UKS health care program.Keywords: Attitude Factor, and UKS Health ServicesÂ